2012
DOI: 10.1021/mp2004498
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Studies on Molecular Dynamics of Two Important Disaccharides: Sucrose and Trehalose

Abstract: Broadband dielectric measurements were carried out in the supercooled as well as in the glassy state of two very important disaccharides: trehalose and sucrose. Multiple relaxation processes were observed. Above the glass transition temperatures of examined disaccharides structural relaxation of cooperative origin was detected, where in the glassy state more local motions (secondary modes) appeared. Our data were discussed in light of the findings reported by other groups. We pointed out that sample preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…(2) The spectrum shown for FD trehalose is representative (at least qualitatively) of the dynamics of both disaccharides in the glassy state (see Supporting Information). The most intense and well-resolved peak has asymmetric shape (HN function with a HN ¼ 0.37; b HN ¼ 0.65) and is identified with the secondary g-relaxation observed by Kaminski et al 56 This process has been related to motions of exocyclic hydroxymethyl groups. 56 The slower process, identified with the secondary b-relaxation by Kamniski et al, 60 is symmetrically broadened (CC function with a HN ¼ 0.44; b HN ¼ 1) and…”
Section: Molecular Dynamics Below the Glass Transitionsupporting
confidence: 52%
See 2 more Smart Citations
“…(2) The spectrum shown for FD trehalose is representative (at least qualitatively) of the dynamics of both disaccharides in the glassy state (see Supporting Information). The most intense and well-resolved peak has asymmetric shape (HN function with a HN ¼ 0.37; b HN ¼ 0.65) and is identified with the secondary g-relaxation observed by Kaminski et al 56 This process has been related to motions of exocyclic hydroxymethyl groups. 56 The slower process, identified with the secondary b-relaxation by Kamniski et al, 60 is symmetrically broadened (CC function with a HN ¼ 0.44; b HN ¼ 1) and…”
Section: Molecular Dynamics Below the Glass Transitionsupporting
confidence: 52%
“…Molecular dynamics of lysozyme, trehalose, and sucrose are the subject of interest for many researchers. [47][48][49][50][51][52][53][54][55][56][57][58][59] It is difficult, however, to understand the relationship between the dynamics of vitreous matrices and the bioprotective effect by analyzing only pure compounds, independently. To tackle this challenge, we focused our study on the dielectric characterization of FD complex formulations Lys þ Treh and Lys þ Sucr, to characterize the molecular dynamics of the vitreous matrix below T g .…”
Section: Molecular Dynamics Below the Glass Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] A broadband dielectric spectroscopic study by Kaminski et al concluded that aqueous sucrose solutions exhibit three different relaxation modes in the low-frequency region, namely, the a ( % 10 À6 s), g ( % 10 À7 s), and b ( % 10 À9 s) relaxation mode. [35] A double-Debye (and/or Cole-Cole) relaxation fitting of dielectric measurements in the 200 MHz-40 GHz region by Fuchs et al [34a] and Weingärtner et al [34b] have extracted two gross relaxation times, which are on the order of approximately 10 ps and approximately 35-45 ps for a 1 m sucrose solution, the former being the rotation of water, whereas the second one is subdiffusive in nature. The focus of our present investigation is the change in the ultrafast collective hydrogen-bond dynamics, which extend up to several hydration layers and leaves its imprint in the terahertz-frequency region only.…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation to this conundrum is that during storage, protein molecules in glassy solids might accumulate small conformational changes that prime them to become increasingly aggregation‐competent upon reconstitution . However, no evidence showing the accumulation of this type of aggregate‐competent species during storage has been presented, perhaps in part because of the relatively low sensitivity of available optical spectroscopies to examine protein structure in dry solids . Aggregation of proteins after lyophilization and reconstitution is often correlated with the extent of loss of native protein structure that occurs during the lyophilization process, with those formulations and conditions that yield the greatest loss of native structure resulting in the most aggregation upon reconstitution .…”
Section: Discussionmentioning
confidence: 99%